RELACIONAMENTO DA IGREJA CATÓLICA COM OS ESTADOS OCIDENTAIS MODERNOS. UM OLHAR SOBRE O PATRIMÓNIO RELIGIOSO - Pérez, Cecilia Andrea Suárez (Cordis: Revista Eletrônica de História Social da Cidade, 2021)
Heritage in America is a cultural, religious and social legacy, whose value has been recognized since the nineteenth century, the processes that are analyzed in this article, based on the particular case of confiscation in Chile, will make known the development of the institutions, the State and its relationship with the Church.